Evaluation of Innovation Ideas Competition in an Efforts to Improve Regional Innovation Index in Singkawang City - Lidya Yuninda Br Barus; Novie Indrawati Sagita (Dinasti Publisher, 2025)
This study aims to evaluate the extent to which the Innovation Idea Competition Program has effectively generated curated, feasible, and impactful ideas that address strategic regional issues, leverage local potential, meet community needs, and contribute meaningfully to the assessment of the Regional Innovation Index. The evaluation employs William N. Dunn’s six policy evaluation criteria as the analytical framework to provide insights for future program enhancement. A descriptive qualitative research method was employed, with data collected through interviews, observations, and document analysis. Informants were selected using purposive sampling techniques to ensure relevance and depth. The findings reveal that, in terms of effectiveness, the program has had limited success in contributing to Regional Innovation Index reporting, with only 38.2% of implemented ideas being reflected in the index, although it has successfully fostered idea generation across various sectors (188 ideas over four years). Budgetary efficiency remains suboptimal, although human resource utilization is deemed adequate due to the commitment of the Regional Development Planning Agency team. Adequacy is also lacking, as the majority of ideas do not sufficiently address core strategic issues. Equity needs to be reinforced, as public engagement in the evaluation process remains minimal despite open access. The program's responsiveness is categorized as